Retalho deslocado lateral associado ao enxerto de tecido conjuntivo no recobrimento radicular - Cardoso, Marina Cremonesi [UNESP] (2018)
The esthetics within dentistry encompasses multidisciplinary procedures, among them, surgical techniques for correction of defects of mucogingival tissues. Gingival recession compromise the esthetics of the smile and cause changes in the periodontal tissues and tooth. Searching for esthetics results and funcional, several are the techniques for covering the exposed root surface. Therefore the present study aims to show a clinical case treated with root coverage associated with lateral displaced flap technique with subepithelial connective tissue graft. A 23 - year - old, female, non - smoker and with good oral hygiene, presented the periodontics discipline of the Faculty of Dentistry of Araçatuba - UNESP, with discomfort during feeding, high and unfavorable esthetics. After surgical treatment and follow-up of the case for 24 months, it was verified that the association of the two techniques obtained a final clinical success of total root coverage, increased range of keratinized gingiva, absence of brushing sensitivity and esthetic satisfaction of the patient